Microstructure and dielectric properties of Zn 3Nb 2O 8 ceramics prepared by a two-stage sintering method - Amonpattaratkit P. (2014)
In this work, the effects of various two-stage sintering schemes on phase formation, microstructural development and dielectric properties of Zn 3Nb 2O 8 ceramics were systematically determined via a combination of scanning electron microscopy (SEM), energy-dispersive X-ray (EDX) and dielectric measurement techniques. In comparison with the conventional sintered samples, it was found that single-phase Zn 3Nb 2O 8 ceramics with maximum density of ∼99% theoretical density, smaller average grain size (∼3 μm) and better dielectric properties can be achieved via a two-stage sintering technique. © 2012 Elsevier Ltd and Techna Group S.r.l.